A construção discursiva de um regime de verdades sobre professores em postagens de 2019 e 2020 no Twitter - VALESCA SOARES CONSOLARO (2021)
Based on archaeogenealogy (ARAÚJO, 2008), the objective of this paper is to destabilize the power-knowledge relationships (FOUCAULT, 2019) that permeate the construction of meanings in ordinary discourses (SILVEIRA, 2015) about Brazilian professors on Twitter, in the years 2019 and 2020. The clippings were selected taking into account the manner in which the discourses of the social network reach an area of visibility that did not exist before the popularization of computerized enunciative spaces (GALLO, 2019). The movement is also based on the discontinuity of historical events (FOUCAULT, 2014a), a view that favors the understanding of how the effects of meaning travel around and are (re)updated in time. The conditions of possibility (FOUCAULT, 2020) of the described and interpreted statements arise from the cut in public higher education funds in 2019, an event marked by the depreciation of the knowledge and practices produced by/at public universities, institutions that were classified by the education minister, Abraham Weintraub, as places of “ruckus”. Based on the establishment of thematic tracks (GUILHAUMOU; MALDIDIER, 2014), three different and interconnected axes were tackled, as methodological-analytical outlines, as follows: “indoctrinating professors”, "being a professor is a statement of not being capable of doing anything else” and “teachers do not work during the pandemic”. As a result, I propose that the analyzed discourses are affected by the formation of a regime of truth (FOUCAULT, 2014a), in which they are applied, through means of governmentality (FOUCAULT, 2019), a strategy of power and knowledge based on disciplinary power (FOUCAULT, 2014b), which fabricates forms of being a teacher today. Keywords: Archaeogenealogy. Ordinary discourses. Ruckus. Subject-teacher.